Comparison between 2D and 3D magnification factors M(k) of welded joints - Yan, Shuanghong (2008)
The present work describes the effort of determining and comparing the 2D and 3D magnification factors Mk of non load-carrying and load-carrying fillet welds, and T-butt welded joints. Mk is one of the terms found in a stress intensity factor equation for any crack. It is defined as the ratio of stress intensity factor of a crack at the weld toe against the stress intensity factor of the same crack geometry at the same plate without any weld. Therefore, it is a measure of the degree of stress concentration factor of the crack. This parameter expressed in an equation for a particular welded joint geometry, can be used to determine the stress intensity factor at the crack toe and hence the fatigue resistance of the welded joint.